Analisis Sengketa Wanprestasi dan Ganti Rugi dalam Kontrak Pengadaan Jasa Ditinjau dari Kitab Undang-Undang Hukum Perdata - Ladyva Rizqina Dinissa; Susilowati Suparto; Etty Haryati Djukardi (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2024)
Contract law plays a key role in trade and business. Failure to fulfill obligations in an agreement, known as default, can include non-fulfillment, delays, or performing actions not aligned with the agreement. The aggrieved party is entitled to seek compensation for the default. In a service agreement case resolved through arbitration, the Respondent was found to have defaulted. Despite both parties agreeing to all terms and performing the contract without objection, the Respondent was ordered to pay compensation under Article 1248 of the Civil Code, which includes the concept of "fraud." The author aims to analyze how default in service procurement is resolved through arbitration and whether the arbitral panel’s decision to impose compensation is justified according to the Civil Code and the contract. The research employs a normative legal approach, focusing on literature and statutory regulations. The findings show that both parties committed default, yet the arbitral panel only adjudicated the Respondent, as the Claimant was not counter-sued. Moreover, the Respondent's actions cannot be classified as fraud. The compensation imposed by the arbitral panel based on Article 1248 of the Civil Code should be seen as abuse of circumstances, not fraud..